EFFECT OF SEDIMENTS ON THE HYDRAULIC PARAMETERS OF THE DUJAILA RIVER IN AL-KUT CITY, IRAQ - Mohammad Abdullah Manati; Jamal Nasser Abdel Rahman (European Journal of Agricultural and Rural Education, 2024)
This study was applied on the Dujaila River that located in Al-Kut city. The study period was for 10 months. Eight sites (sections) of the river were chosen. The distance between one site and another was 1000 m. The longitudinal section of the river was divided into 8 vertical sections on the river course, starting from the gates of the River. The discharge and speed of the water current for the studied sections were measured using a portable M9 device on a boat belonging to the Kut Dam Department and connected to a laptop computer. The result showed that there was a difference in the rates of the engineering standards of the Dujaila River during the research period, as it ranged between 8.16 m³/s -1 to 13.25 m³/s -1 , 0.13- 0.23 m³/s -1 , 39.25- 81.02 m² and 0.92- 1.29 m for each of Water discharge, water current speed, cross-sectional area of river flow, and depth of water level, respectively. Statistical analysis of the results showed that there is a positive correlation (r=0.969) between water discharge and suspended sediment load. Also, there is a positive correlation (r=0.629) between water discharge and the concentration rate of suspended sediments. The results indicated that there is a positive correlation (r = 0.95) between the average suspended sediment concentration (TSS) and turbidity, and a positive correlation (r = 0.79) between the suspended sediment load (TSS) and turbidity